Hubungan Antara Efektivitas Manajemen Informasi Sekolah dan Ketercapaian Tujuan Pendidikan Agama Islam Pada Sekolah Dasar - Aulia Hafizoh; Risnawati; Granita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The achievement of Islamic Religious Education (PAI) goals in elementary schools often faces challenges due to ineffective school information management. Academic data, information administration, and learning evaluation that are not optimally managed can affect lesson planning and the attainment of PAI objectives, including aspects of knowledge, attitudes, and students’ religious practices. This issue is an important concern for improving the quality of PAI in private elementary schools in Pekanbaru. This study aims to examine the relationship between the effectiveness of school information management and the achievement of Islamic Religious Education goals. The research uses a quantitative approach with a correlational design. The population of this study includes all PAI teachers in the elementary school, with a sample of 10 teachers as respondents. Data were collected using a closed-ended questionnaire with a five-point Likert scale and analyzed using descriptive statistics and the Pearson Product Moment correlation test. The results show that the effectiveness of school information management is in the high category, as is the achievement of PAI objectives, which is relatively optimal. Correlation analysis indicates a positive and significant relationship (r = 0.684, p < 0.05) between the effectiveness of school information management and the achievement of PAI goals. In conclusion, the more effective the school information management, the higher the achievement of Islamic Religious Education objectives, making school information management an important strategic instrument in supporting the success of PAI learning in elementary schools.